Problematika Mahasiswi Program Tahfidz Al-Qur’an di Ma’had Darul Hikmah Iain Kediri - Risna Zamzamy; M. Miftakhul Huda; Majidatul Muyasaroh; Affan Nur Habib (Halaqa: Islamic Education Journal, 2018)
Memorizing Alqur'an is not as easy as turning the palm of the hand, there are many obstacles or small difficulties faced by the memorizers of the Koran. Preferred pronunciation and makhroj, because errors in pronunciation will be fatal, because it can change the meaning and meaning. In this study discuss the benefits and advantages of memorizing the Qur'an, the problems faced by the students of the Tahfidzul Qur'an program Ma'had Darul Hikmah IAIN Kediri, the tips of santri to overcome the problems encountered during the Tahfidz al-Qur'an program in Ma'had Darul Hikmah IAIN Kediri, and also specific tips for the Qur'anic followers. In this study, researchers used a qualitative approach that was descriptive qualitative because the data obtained in this study were in the form of words and was a study aimed at describing and analyzing symptoms or phenomena, events, social activities, attitudes, beliefs, perceptions, people's thoughts individually or in groups that occur in the field.The results showed that the benefits of memorizing the Koran include happiness both in the world and in the hereafter, peace of mind or peace of mind, sharp memories and intuition, having a good identity and behaving honestly, being fluent in speaking and having a certain prayer.